2013
DOI: 10.1007/s10151-013-1073-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-expanding metal stent insertion by colorectal surgeons in the management of obstructing colorectal cancers: a 6-year experience

Abstract: SEMSs insertion is a safe and effective technique for colonic decompression in the setting of acute malignant large bowel obstruction as either a palliative measure or as a bridge to subsequent resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…It is suggested that there is no statistically signi cant difference in 30-day mortality between the BTS group and ES group in AMCO of 5 randomized controlled trials [27] similar to data from our center that both of the 30-day mortality rate and 30-day readmission rate of 258 patients successfully proceeded to resection in BTS were 0%. In a recent retrospective longitudinal cohort study using the NYS SPARCS Database compared stenting as a BTS with immediate resection, found that colonic stenting as a bridge to surgery lead to less stoma creation a signi cant quality of life advantage [28] and lower complication rate [24] , consistent with the results of our study that no signi cant and serious postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is suggested that there is no statistically signi cant difference in 30-day mortality between the BTS group and ES group in AMCO of 5 randomized controlled trials [27] similar to data from our center that both of the 30-day mortality rate and 30-day readmission rate of 258 patients successfully proceeded to resection in BTS were 0%. In a recent retrospective longitudinal cohort study using the NYS SPARCS Database compared stenting as a BTS with immediate resection, found that colonic stenting as a bridge to surgery lead to less stoma creation a signi cant quality of life advantage [28] and lower complication rate [24] , consistent with the results of our study that no signi cant and serious postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent meta-analysis of studies nding stentrelated perforation is associated with an increased risk of global and locoregional recurrence by Izaskun Balciscueta et al [22] . Although some studies suggest that no negative effects on survival were observed for stentrelated perforations [23] , perforation itself is a dangerous event necessitating an emergency surgical intervention [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonic stenting as a bridge to elective surgery in obstructive colorectal cancer has been widely used during the last decade because it can prevent high-risk emergent surgery providing time for patient stabilization, staging workup and appropriate bowel preparation before elective surgery. 7 , 8 Several studies compared the efficacy and safety of SEMS insertion as a bridge to elective surgery vs emergency surgery for acute left-sided malignant colonic obstruction. 9 , 10 , 11 Recent meta-analysis showed lower rates of permanent stoma formation, higher rate of successful primary anastomosis and more favorable overall morbidity, with no statistically significant difference in the postoperative mortality between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Preoperative SEMS placement can prevent high-risk emergent surgery allowing patient stabilization and staging workup before surgical intervention. 7 , 8 This approach showed more favorable short-term outcomes in terms of permanent stoma formation, primary anastomosis and overall morbidity and similar postoperative mortality when compared to emergent surgery. 9 , 10 , 11 However, a Dutch multicentric randomized trial showed an increased morbidity and mortality in the group of patients with SEMS as bridge to surgery when compared to the surgical approach and due to these interim results the study was interrupted.…”
Section: Introductionmentioning
confidence: 91%